Wakaf Uang Solusi Alternatif Memberdayakan Ekonomi Umat Studi Kasus Pada BMT Mandiri Sejahtera Karangcangkring Jawa Timur - Misbahul Khoir (Universitas Islam Lamongan, 2018)
Bayt al-Mal wa al-Tamwil (BMT) is a microfinance institution that is operated with profit sharing or sharia principle by developing micro and small businesses, in order to elevate degrees and dignity and defend the interests of the poor. BMT (Baitul Mal Wat Tamwil) also receives deposits from zakat, waqf, infaq and sadaqah funds and optimizes its distribution in accordance with its regulations and mandates. The concept of money or cash waqf even though only with 10,000 nominal customer however, endowments have enormous potential to be explored and developed with an emphasis on how the potential of money waqf can be an alternative solution in order to empower the ummah economy through BMT Mandiri Sejahtera Karangcangkring East Java. This BMT Mandiri Sejahtera Karangcangkring in East Java outlines the types of products classified into three, namely savings, financing and services. There are three deposits: Simaster, Hajj and Umrah savings, and qurban savings. There are five financing, namely murabahah, rahn, mudlarabah, musharakah, and ijarah. While service products such as exchange of ringgit money, remittances from within / abroad, PLN online payments, Token, Telkom, FIF, BAF, Adira Finance, Oto Finace, WOM Finance, STNK/mutation installment installments. Although there are weaknesses, the result of research shows that the threat that is feared will hamper the endowment of money products on Mandiri Sejahtera BMT but this is not a burden, the most important is that this product does not violate the rules of sharia and is permissible in Islam because the application of money waqf products in Mandiri Sejahtera BMT is appropriate, namely the value the principal remains and the remaining proceeds from the money endowments will be distributed for virtue. Keywords: Cash Waqf, Society Economic Empowerment, BMT Mandiri Sejahtera